2011
DOI: 10.1021/jf201139e
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Properties of Green Tea Extract Protect Reduced Fat Soft Cheese against Oxidation Induced by Light Exposure

Abstract: The effect of two different antioxidants, EDTA and green tea extract (GTE), used individually or in combination, on the light-induced oxidation of reduced fat soft cheeses (0.2 and 6% fat) was investigated. In samples with 0.2% fat, lipid hydroperoxides as primary lipid oxidation products were not detected, but their interference was suggested from the formation of secondary lipid oxidation products such as hexanal and heptanal. The occurrence of these oxidation markers was inhibited by spiking with 50 ppm EDT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 34 publications
2
20
0
Order By: Relevance
“…food matrices [150,151]. However, these radicals show quite short lives unless very low temperatures are guaranteed [13,[151][152].…”
Section: Magnetic Resonancementioning
confidence: 99%
See 1 more Smart Citation
“…food matrices [150,151]. However, these radicals show quite short lives unless very low temperatures are guaranteed [13,[151][152].…”
Section: Magnetic Resonancementioning
confidence: 99%
“…However, these radicals show quite short lives unless very low temperatures are guaranteed [13,[151][152]. In an attempt to avoid this problem, some recently developed methodologies deal with the detection of unstable free radicals.…”
Section: Magnetic Resonancementioning
confidence: 99%
“…Han et al (2011) and Huvaere et al (2011) reported that the addition of some polyphenols, including catechins, affected the composition of curds and cheese due to possible interactions between milk components and catechins. These catechins may interact non-covalently with proteins, such as through hydrophobic association (Yuksel et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The manufacture of a functional cheese product containing nutritionally important amounts of phenolic compounds from natural sources such as fruits and vegetables with increased AA is possible, although bioavailability, health benefits, toxicity at high concentrations and sensory aspects need to be considered. Only a few studies have reported on the effects of polyphenols in milk gels and curds, including the effects of individual phenolic compounds in rennet curds (Han et al ., ,b), the fortification of soft cheese with rosemary extract (Hala et al ., ) and the decrease in lipid oxidation‐derived aldehydes and improved flavour stability due to green tea extracts in soft cheese (Huvaere et al ., ). There are also reports on the inherent AA and phenolic content of cheese in the absence of polyphenolic supplementation (Shaiban et al ., ; Gupta et al ., ; Hilario et al ., ; Han et al ., 2011a).…”
Section: Introductionmentioning
confidence: 99%